Search for Mycobacterium avium Subspecies paratuberculosis Antigens for the Diagnosis of Paratuberculosis - Mon, Maria Laura (2012)
The aim of this study was to evaluate a wide panel of antigens of Mycobacterium avium subsp. paratuberculosis (MAP) to select candidates for the diagnosis of paratuberculosis (PTB). A total of 54 recombinant proteins were spotted onto nitrocellulose membranes and exposed to sera from animals with PTB (n = 25), healthy animals (n = 10), and animals experimentally infected with M. bovis (n = 8). This initial screening allowed us to select seven antigens: MAP 2513, MAP 1693, MAP 2020, MAP 0038, MAP 1272, MAP 0209c, and MAP 0210c, which reacted with sera from animals with PTB and showed little cross-reactivity with sera from healthy animals and animals experimentally infected with M. bovis. The second step was to evaluate the antigen cocktail of these seven antigens by ELISA. For this evaluation, we used sera from animals with PTB (n = 25), healthy animals (n = 26), and animals experimentally infected with M. bovis (n = 17). Using ELISA, the cocktail of the seven selected MAP antigens reacted with sera from 18 of the 25 animals with PTB and did not exhibit cross-reactivity with healthy animals and only low reactivity with animals with bovine tuberculosis. The combined application of these antigens could form part of a test which may help in the diagnosis of PTB.